Pengaruh Fire Safety Games Terhadap Persepsi Mahasiswa Vokasi Terhadap Fire Safety Berdasarkan Health Belief Model - Meisi Riana; Antinah Latif; Elviana, Elviana (Ikatan Dosen Menulis, 2024)
Background. Awareness of fire prevention needs to be instilled in vocational students as young workers who will be involved in the industry. Games are a learning method with great potential to help complement and strengthen material, make it fun, active, effective, motivate, and entertain in order to improve learning outcomes. Awareness of fire safety is not only influenced by knowledge but also influenced by perception, so it is necessary to examine how the impact of games on student perceptions based on the heath belief model (HBM) on fire safet Aim. The research aims to determine the impact of fire-safe games on students' perceptions of fire safety based on the health belief model theory. Method. The method used is quasi-experimental with a nonequivalent control group pretest-posttest research design. Subjects were 30 students majoring in graphic engineering. Measurements were taken before and after the action. The measuring instrument used was a validated and reliable HBM-based perception questionnaire with Likert’s Scale. The analysis used is the Wilcoxon statistical test Result. Wilcoxon test for the perception of the pre and post test treatment groups shows that the perception of benefit experiences a significant difference because the p value is less than 0,05 this shows that fire safety games can influence the perception of benefits on the use of fire extinguishers